OPTIMIZATION DESIGN OF GROUND GRID MESH OF 132/33KV SUBSTATION USING ETAP (Nigerian Journal of Technology, 2016)
This paper presents ground grid mesh design analysis and optimization of a 132/33kV substation. Ground grid mesh is made up of horizontal and vertical conductors connected with vertical rods buried under substation ground. The function of this structure is to effectively dissipate extremely high current generated in the system. The objective of this study is to determine the cost effective and safe ground grid mesh parameters by comparing mesh design analysis using IEEE and Finite Element Analysis (FEM) methods. The two methods are used differently to determine the ground grid mesh parameters, step & touch voltages, horizontal and vertical number of conductors, vertical numbers of rods, and final substation Resistance. Etap 12.60 software is used for the analysis. Firstly, expected maximum short circuit current of OHIA 132/33kV substation is determined. Secondly, analysis is performed to determine input and output parameters of grid mesh structure using IEEE and FEM methods. An optimized result of IEEE method is determined. Analysis of both results is shown in different tables and recommendation is given regarding the best method for the grid mesh design.  http://dx.doi.org/10.4314/njt.v35i4.30